Effect of music therapy on postembolization syndrome in Thai patients with hepatocellular carcinoma: A quasi-experimental crossover study - Wassana Khuntee; Kanitha Hanprasitkam; Bualuang Sumdaengrit (Belitung Raya Foundation, Indonesia, 2022)
Background: Postembolization syndrome (PES), including abdominal pain, nausea, and vomiting, are complications most severe on the first day after transarterial chemoembolization (TACE). Music therapy has been found to help manage pain. If pain, a cause of nausea and vomiting, can be relieved, then nausea and vomiting should also be reduced. Objectives: This study aimed to examine the effect of music therapy on PES in patients with liver cancer after receiving TACE. Methods: This study employed a quasi-experimental crossover design. The study was conducted at the inpatient units of a specialized hospital for cancer in Bangkok, Thailand, from March 2020 to October 2021. Thirty patients with liver cancer were purposively selected based on the pre-determined criteria. A change-over design was used to compare patients’ changes in abdominal pain, nausea, and vomiting from the experimental period to the other control period. During the experimental period, music therapy was administered for 30 minutes on Day 0 after TACE, then twice a day in the morning and evening of Days 1 and 2 after TACE, and in the morning of Day 3 after TACE. During the control period, the patients used silent headphones. Data were analyzed using Wilcoxon signed ranks and Friedman tests. Results: The participants perceived abdominal pain, nausea, and vomiting at a mild level during all periods. Pain scores in the music therapy period were significantly lower than those in the control period on Days 0, 1, and 2 after TACE (p <0.001, p <0.01, and p <0.001, respectively) and lower than at the baseline (p <0.001). There were no statistically significant differences in nausea and vomiting scores between the music therapy period and the control period on Days 0, 1, and 2 after TACE and no statistically significant differences at the baseline. Conclusion: Music therapy effectively reduces mild pain among patients with liver cancer experiencing PES. This therapy can be used as a non-pharmacological treatment for nurses and other healthcare professionals in caring for patients with liver cancer.